Comparison of changes in different characteristics of Arrowroot (Maranta arundinacea) flour stored under ambient (27 °C) and refrigerated (4 °C) conditions (IPS Journal of Nutrition and Food Science, 2023)
Arrowroot (Maranta arundincea) is an underutilized gluten-free flour source in Sri Lanka. The purpose of this study was aimed to evaluate the physicochemical properties and microbiological safety of arrowroot flour while it was stored at room temperature (27 °C) and refrigerated (4 °C) for a year. Moisture content (%), water activity (aw), colour in L*a*b* values, and microbial load (log cfu/g) were assessed. Before storage, arrowroot flour was extracted from rhizomes and packed into LDPE bags. The moisture content, water activity, and colour of arrowroot flour were found to be significantly affected by storage conditions. The moisture content and water activity of flour stored under both conditions increased, while L* values decreased over time.  Microbial growth was also observed, with ambient storage having a higher microbial load than refrigerated storage. The study contributes to the development of quality standards for arrowroot flour by providing important information on its shelf life. It also emphasizes the significance of refrigerated storage conditions to ensure the safety and quality of arrowroot flour for consumption.
Keywords: Arrowroot; Colour Maranta arundinacea; Microbiological assessment